PEMBERDAYAAN PARIWISATA BUDAYA KARO MELALUI "TOPENG TEMBUT-TEMBUT" SEBAGAI UPAYA MENINGKATKAN EKSISTENSI WARISAN BUDAYA - Syamsul Arif; Lasenna Siallagan; Novita Eka Fitri; Taufik Panjaitan; Difa Hartati; Erika C.P Silitonga; Yulisin Nazra (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
Tembut-Tembut Masks are part of the cultural heritage of the Karo people in North Sumatra,holding deep historical and spiritual significance. However, their existence is increasinglythreatened by modernization and the declining interest of younger generations in this culturalheritage. This study aims to explore strategies for empowering Karo cultural tourism throughTembut-Tembut Masks, with a focus on preserving their cultural and spiritual values. Aqualitative approach using literature review methodology was employed to collect andanalyze data. The findings indicate that empowering Karo cultural tourism throughTembut-Tembut Masks can be achieved through the integration of community-based tourism,the Penta Helix model, and digital innovation. These strategies not only enhance theexistence of the Tembut-Tembut Masks but also have the potential to support local economicdevelopment and strengthen Karo cultural identity. Keywords: Tembut-Tembut Masks, cultural heritage, cultural tourism, community empowerment, Karo, cultural preservation